Theoretical investigation of the energy of olefin-and sila-olefin insertion/β-H elimination reactions of two late transition metals - DFT MO calculations - Ferro, Rita Leonor Veiga da Silva e Veiga, 1979- (2014)
Tese de doutoramento, Química (Química Inorgânica), Universidade de Lisboa, Faculdade de Ciências, 2013